Living Indefinitely and Living Fully: Laudato Si' and the Value of the Present in Christian, Stoic, and Transhumanist Temporalities - Scherz, Paul J. (Theological studies, 2018)
Transhumanism promises to overcome human finitude by indefinitely extending human life, enabling a vast increase in valuable experiences. Yet transhumanism depends on social processes of what Pope Francis calls rapidification and sociologists call social acceleration, which are causing people to experience a lack of time, driven by increasing speed of work and fears of missing out on opportunities for enjoyment. In contrast, Francis and the Stoics encourage people to confront finitude by flourishing through a qualitative transformation of character marked by a temporality focused on God's providential presence and on serving the present needs of others.